ENGLISH LEARNING SRATEGIES USED BY JAPANESE LANGUAGE EDUCATION STUDY PROGRAM STUDENTS - Widiastuti, Sang Ayu Putu Sri Anggrita; Sari, Rima Andriani; Marsakawati, Ni Putu Era (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study was aimed to investigate the Language Learning Strategies (LLS) used by university students in learning English and the factors that affect the choice of the strategies by students from the Japanese Language Education at a public university in Bali. This research utilized mixed method in its process. There were 55 active students from the Japanese Language Education study program participated in this research. Data were collected through the SILL version 7.0 questionnaire developed by Oxford and has gone through an adaptation process in accordance with the times, and was validated by 2 experts. The questionnaire consists of 47 statements that have six LLS categories namely memory, cognitive, compensation. metacognitive, affective, and social. To find out the tendency of using LLS and also the factors that influence the use and selection of LLS, data analysis was carried out through Microsoft Excel. The results showed that of the six strategies in the English learning process of university students, all strategies are used by the students with high frequency, except compensation strategy with medium frequency. Factors that influence the selection of LLS is GPA.